Tire and rubber particles in the environment—A case study from a hot arid region - Habib, Rana Zeeshan; Al Kendi, Ruwaya; Ghebremedhin, Furtuna; Elkashlan, Marim; Iftikhar, Syed Haris; Poulose, Vijo; Ramachandran, Tholkappiyan; Mourad, Abdel-Hamid Ismail; Hamed, Fathalla; Thiemann, Thies (Frontiers in Environmental Science, 2022)
Materials made of rubber are a source of polymers released into the environment, where tire abrasions are a major contributor. In many hot, arid environs, whole tire losses are more common than in moderate climates, and lead to the accumulation of additional tire material on road sides, which over time can be the source of secondary micro-tires. Other rubber containing material from cars such as mud-flaps and floor mats has been seen as an appreciable additional source of micro-rubber. Due to the lack of precipitation, it is expected that modes of micro-tire relocation are more limited in arid regions than in more moderate climates. This 2-year study examines the rubber/tire content from 34 sampling sites within the region of Al Ain, Eastern region of Abu Dhabi Emirate, United Arab Emirates. The samplings include road dust, soil along roadsides, storm water run-off samples and samples collected in Wadis (creek beds that seasonally carry water) and one artificial lake. The mean average number of micro-tires in road dust was found to be 44.4 micro-tires/g. In soil samples alongside the roads, it was 22.8 micro-tires/g. The mean average size of micro-tires for all 34 sampling sites was found to be 106.9 µm. It could be seen that rubber/tire materials desiccate over time during the high temperatures of the Emirati summer, become hard, brittle and break into smaller pieces, resulting in secondary micro-tire particles. The study of run-offs showed that tire particles are swept into storm drains during larger, very infrequently occurring rain events. However, the predominant mode of micro-tire transport was found to be on road by physical contact with cars, off-road by a combination of physical contact with moving objects and air movement. Samples taken from an artificial lake and three Wadis within the confines of Al Ain have shown only few micro-tire particles, so that the dispersion of micro-tires is not as pervasive as had been expected prior to this study.